Undetected isoniazid mono resistance in rural Eastern Cape Province - A risk for the emergence of multidrug-resistant TB - Van der Merwe, Charnay Janine (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.